Filipino tribal religious experience, No. 2 : sickness, death and after-death - Kiley, Henry W.; editor; Giraffe Books (Quezon City : Giraffe Books, 1994)
"Proceedings of the second annual colloqium between social scientist and theologians."
Keywords: Ethnic groups of the Philippines -- Death; Ethnic groups of the Philippines -- Social life and customs; Sickness -- Religious life